Thinking Through the Box: Evaluating a 3D Game to Engage Penetrative Thinking - Pathak, Aarohi; Chang, Jack S. K.; Resch, Gabby; Doucette, Alison; Yeboah, Georgina; Welsh, Timothy Nevin; Nitsche, Michael; Mazalek, Ali (Frontiers in Virtual Reality, 2020)
Spatial skills allow us to mentally imagine and manipulate objects and their spatial relations. These skills are crucial in both every day and expert tasks. The present paper reports on an evaluation of a 3D game developed to train a specific spatial skill known as penetrative thinking—the ability to imagine cross-sections of 3D objects from their surface features. In the game, users change the location and orientation of a virtual plane to make cuts through 3D objects in a series of spatial puzzles. Users operate an interface to position the virtual plane until a “slice” at the location of the plane matches a target cross-section of a virtual object. Multiple spatial puzzles with different properties are completed throughout the game. In one version of the game, users completed the puzzles in an immersive virtual environment and operated a tangible interface to move the virtual plane. A secondary version of the game required users to view the puzzles in a virtual environment displayed on a computer screen, and to position the slicing plane with a keyboard and mouse. Participants (n = 45) completed a measure of penetrative thinking (Santa Barbara Solids Test) before and after completing one of three interventions: the game with the tangible interface (n = 15), the game with the keyboard interface (n = 15), or a series of (control) questions (n = 15). Although there were no significant pre-/post-intervention changes in penetrative thinking in any of the groups, participants' performance in the game correlated with scores on a standardized test of penetrative thinking. These results provide evidence that the game and the standardized test accessed similar spatial skills and, as a consequence, indicate that the 3D game has the potential to be a valid approach for training penetrative thinking skills.